A SYSTEMATIC REVIEW OF THE INFLUENCE OF INFORMATION SYSTEM IMPLEMENTATION ON THE EFFECTIVENESS OF KNOWLEDGE RETRIEVAL IN THE ARCHIVAL CONTEXT - Ade Maya Azkiyati; Muhamad Prabu Wibowo; Tamara Adriani Salim; Mad Khir Johari Abdullah Sani (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
In the era of digital transformation, archival institutions increasingly rely on information systems to ensure sustainable access to organizational knowledge. The effectiveness of knowledge retrieval in archival systems has become increasingly critical in the digital era. However, existing studies remain fragmented, with limited integrative analysis of technological, organizational, and user-related factors. This study addresses this gap by systematically reviewing the influence of information system implementation on knowledge retrieval effectiveness in archival contexts. A Systematic Literature Review (SLR) was conducted on 28 peer-reviewed articles indexed in Scopus and Taylor & Francis, published between 2015 and 2025. The selected studies were analyzed using a structured classification approach to identify key variables, measurement indicators, and implementation challenges. The findings reveal that knowledge retrieval effectiveness is shaped by five interconnected dimensions: digital infrastructure transformation, metadata standardization, system interoperability, retrieval system integration, and cross-professional collaboration. Effectiveness is commonly assessed using retrieval performance metrics, metadata quality, user interface, user experience, and data accessibility. Despite these advancements, persistent challenges continue to hinder optimal system performance. This study contributes to the literature by proposing an integrative analytical perspective that links technological, organizational, and user-centered dimensions in evaluating archival knowledge retrieval, thereby addressing the lack of synthesis in prior research. The results highlight that successful implementation depends not only on technological capability but also on alignment with governance structures and user readiness. These findings have practical implications for archival institutions and policymakers in designing adaptive, interoperable, and user-oriented information systems to enhance sustainable access to knowledge